(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Una premessa - 2. Libertà religiosa e secolarizzazione - 3. L’odierna crisi della libertà religiosa - 4. Secolarismo e libertà religiosa - 5. Conclusione. Religious freedom and secularism ABSTRACT: The essay questions about the singular phenomenon for which, in front of the numerous and serious violations that are daily perpetrated in the world, towards the right of religious freedom, the West appears so detached and generally reluctant to political and diplomatic intervention. The fact is even more singular, if one compares this phenomenon with the general commitment that the West demonstrates for the planetary affirmation of the human rights, in a spirit almost of proselytism. In the opinion of the Author, the inactivity must be connected to the dominant secularist culture that has removed the sacred from the horizon of human meaning, with the consequence of the insignificance of the religious sentiment, of the irrelevance of the religious practice and, therefore, of the unreasonableness of fighting for their survival.